Environmental Impact Assessment of River Ganga along the Ghats of Varanasi City - Yadav, Shweta; Rashmi; Ram Bilas (National Geographical Journal of India, 2022)
Water is the most important element in the biosphere because on the one hand it is vital for the maintenance of all life forms and on the other hand it helps in the movement, circulation and cycling of nutrients in the biosphere. Water is also essential for power generation, navigation, irrigation of crops, disposal of sewage etc. Increased demand of water consequent upon increasing population and industrial expansion has degraded the quality of water considerably. Though water like other natural substances has self purifying mechanism during recycling process but when the amount of foreign undesirable substances added by the man to the water exceeds the tolerance level and self purifying mechanism of water, it gets polluted. Varanasi, the most ancient city in the world also suffers from the problem of water pollution. The main sources of water pollution in Varanasi city is the domestic waste water which flows through sewers and open drains. Total volume of domestic wastewater generated in the city is estimated to about 300 MLD of which only 102 MLD is treated in sewage treatment plants (STPs) and the remaining 198 MLD is directly discharged into river Ganga and Varuna through open drains. The STPs do not work efficiently or properly during rainy season and many other reasons increase the pollution load of river Ganga and Varuna. Regular huge quantity of domestic wastewater either drains into river Ganga without any treatment or disposed on open lands further polluting underground water through seepage which affect the quality of water and human health also. To assess the human responses towards the problems of water pollution a total number of 540 respondents were interviewed by using the structured questionnaire blended with suitable open-ended questions